MicroRNA‐153‐3p increases autophagy in sevoflurane‐preconditioned mice to protect against ischaemic/reperfusion injury after knee arthroplasty. Issue 9 (2nd April 2020) - Qiu, Shuang; Liu, Benjuan; Mo, Yanshuai; Wang, Xueqin; Zhong, Lina; Han, Xiao; Mi, Fuli
Abstract: The use of tourniquet during total knee arthroplasty (TKA) can result in ischaemia/reperfusion injury (IRI). Of interest, microRNAs (miRs) are reported to be involved in various kinds of IRI due to their ability in modulating autophagy. Therefore, the study aimed to investigate the effect of miR‐153‐3p on autophagy in IRI in vitro and in vivo under sevoflurane preconditioning. In the in vitro model, chondrocytes from naive mice were treated with 0% FBS alone or in combination with sevoflurane. Additionally, in vivo assays were conducted in mouse models with tourniquet‐induced IRI after TKA under or without sevoflurane preconditioning. The pathological observation in vivo validated that sevoflurane preconditioning protected the knee joint against IRI. Moreover, miR‐153‐3p expression was diminished in chondrocytes of the in vitro model and in cartilage tissue of the in vivo model, but its expression was appreciably up‐regulated in the presence of sevoflurane preconditioning. Mechanistic study showed that miR‐153‐3p disrupted the interaction between Bcl‐2 and Beclin1 by targeting Bcl‐2, thereby facilitating autophagy in chondrocytes under sevoflurane preconditioning. Furthermore, the experiments in human chondrocytes also verified the protective effects of miR‐153‐3p against IRI were realized through inhibiting Bcl‐2. Collectively, miR‐153‐3p overexpression blocks the interaction between Bcl‐2 and Beclin1 via down‐regulation of Bcl‐2 to promote autophagy of chondrocytes, thus protecting knee joint against IRI after TKA under sevoflurane preconditioning.